Workforce quality goals and the implications for education: The Oregon experience. - Sivers-Boyce, Nathan; Hibbard, Tom; Gray, Jerry (Education Policy Analysis Archives, 2005)
We review a plan that attracted the attention of public sector planners everywhere, Oregon's 1989 Oregon Shines: An Economic Strategy for the Pacific Century. In particular, we focus on Oregon's aspirations for world-class workforce quality; a status that the state's planners argued would contribute to a host of other outcomes that foster citizen well-being. The broader purpose of the paper is to emphasize the importance of timing. Planners must remain mindful of the long timeframe required for educational improvements to directly benefit the economy. We begin by reviewing the arguments that planners offered for the centrality of workforce quality. Second, we briefly review a few indicators of the state's commitment to achieving a world-class workforce and the consequences of this commitment to date. Third, we show that failure to dynamically model the linkages between actions and outcomes led to adoption of a workforce goal that was unattainable even if commitment had been Herculean. Finally, we consider other planning targets that might be improved by understanding why Oregon's workforce quality goals were unachievable.